Occupational Asthma -- The Last 50 Years - Moira Chan-yeung (Canadian Respiratory Journal)
It was indeed a great honour for me to be this year's Christie Memorial Lecturer. Although I have not been fortunate enough to have had personal contact with Professor Christie, one of the greatest lung physiologists of our time, I have had the opportunity over the years of interacting with and learning from the group working in the laboratory named after him - the Meakins-Christie Laboratories - as a member of the Respiratory Health Network of Centres of Excellence, Canada.